Research and practice on self-service terminal in smart campus - Cheng-jie XING; Ling YUAN; Xu YANG; Tian-ping LAI; Zhi-kun ZHANG (Tongxin xuebao)
Aiming at construction of smart campus,a solution of using self-service terminal to provide intelligent service for campus users was proposed.The features of smart campus and the concept of self-service were expounded.The self-service terminal applications on campus was analyzed.An architecture was designed,including terminal hardware,terminal software,supporting software for monitoring and management,external services interface etc.Used it as a blueprint for the development of a self-service terminal system on Peking University campus.Practices shows that self-service terminal system improves the intelligence level and efficiency of campus services.